How Doctors Care for Others: Caring, Being with and Making the Difference (Global Journal of Human-Social Science, 2020)
Although more frequent and intense on infancy, the attachment system can be triggered across the lifespan, from "the cradle to the grave." In adulthood, whenever the individual's internal working model does not have enough resources to sustain his/her insecurity, one seeks support from an attachment figure. Illness may trigger the attachment system, obliging the individual to pursue the proximity of an attachment figure. In our research on how the doctor's attachment style affects the doctor-patient relationship (Barstad-Castro Neves, 2018), we assessed the doctor's attachment style and correlated with a semi-structured interview script. One of the categories highlighted in our research was how physicians cared for their patients. The present article aims to explore, expand, and clarify the category mentioned. It is essential to discuss how the car ing and concerning doctor acts towards his/her patient, and how the caregiving system, from the lens of attachment theory, has a functio n in that matter. Our research may contribute to the discussion of strategies to improve the doctor-patient relationship, therefore refining patient adherence and compliance to treatment. Besides, it can also shed light on how to give support to medical professionals, starting from medical school.
Keywords: attachment theory; doctors; bedside manners; caregiving system